2017
DOI: 10.1021/jacs.6b13096
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stabilization of Metal Oxide–Water Interfaces

Abstract: ABSTRACT:The interaction of water with metal oxide surfaces plays a crucial role in the catalytic and geochemical behavior of metal oxides. In a vast majority of studies, the interfacial structure is assumed to arise from a relatively static lowest energy configuration of atoms, even at room temperature. Using hematite (-Fe2O3) as a model oxide, we show through a direct comparison of in situ synchrotron X-ray scattering with density functional theorybased molecular dynamics (DFT-MD) simulations that the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 49 publications
5
71
2
2
Order By: Relevance
“…[46][47][48] This method has been successfully applied to several mineral-water interfaces, 31,[49][50][51][52] but not to the HLWI, which is challenging to simulate due to the open-shell 3d orbital character underlying the antiferromagnetic spin pattern of hematite. We obtain pK a values for the half-layer terminated (012) surface species directly from DFT-MD simulations at GGA+U level with dispersion corrections, that are in good agreement with the recent BVT estimates by McBriarty et al 20 based on X-ray crystal truncation rod (CTR) diffraction data. Both our calculations and recent BVT estimates suggest that the deprotonation of these surfaces require significantly more free energy input than previously thought.…”
supporting
confidence: 87%
“…[46][47][48] This method has been successfully applied to several mineral-water interfaces, 31,[49][50][51][52] but not to the HLWI, which is challenging to simulate due to the open-shell 3d orbital character underlying the antiferromagnetic spin pattern of hematite. We obtain pK a values for the half-layer terminated (012) surface species directly from DFT-MD simulations at GGA+U level with dispersion corrections, that are in good agreement with the recent BVT estimates by McBriarty et al 20 based on X-ray crystal truncation rod (CTR) diffraction data. Both our calculations and recent BVT estimates suggest that the deprotonation of these surfaces require significantly more free energy input than previously thought.…”
supporting
confidence: 87%
“…With different types of preparation, such as chemical etching, hydroxylated surface models with missing cations are also reported to be stable in these conditions. 32,7173 …”
Section: Discussionmentioning
confidence: 99%
“…2 As a rapid charge transport and transfer between the back substrate, photoactive semiconductor, the catalyst and electrolyte is necessary for efficient STH performance, the electronic and structural properties of back substrate/semiconductor/catalyst/electrolyte interfaces play a vital role in PEC performance. [5][6][7][8][9][10] The electron-hole recombination at the interface of the back substrate and hematite is critical for the electron transport from bulk hematite to the current collector and thus affects the overall PEC photocurrent response. 2,9,[11][12][13][14] For instance, Zheng et al reported an integrated hematite, TiO x and FeOOH photoanode and obtained a photocurrent around 1.5 mA cm -2 , which is still much lower than the theoretical value (12.5 mA cm -2 ) of hematite.…”
Section: Introductionmentioning
confidence: 99%